Prevalence of mental distress among adult survivors of childhood cancer in Germany—Compared to the general population. (6th March 2019) - Burghardt, Juliane; Klein, Eva; Brähler, Elmar; Ernst, Mareike; Schneider, Astrid; Eckerle, Susan; Neu, Marie Astrid; Wingerter, Arthur; Henninger, Nicole; Panova‐Noeva, Marina; Prochaska, Jürgen; Wild, Philipp; et al.
Abstract: Background: Increasing survival rates after childhood cancer have raised the issue of long‐term mental health consequences in adulthood. This study determines mental health distress among long‐term survivors of pediatric cancer and compares it to control groups. Methods: Childhood cancer survivors (CCS; N = 951, aged 24‐49 years) were compared to three age‐matched control groups from the general population collected at three time points. The study compared the prevalence of clinically relevant symptoms of a wide range of common mental disorders (depression, somatic distress, suicidal ideation, generalized anxiety, panic, social anxiety, and sleep disturbances) using identical, validated questionnaires. CCS were identified by the German Childhood Cancer Registry. Controls were approached by a demographic consultation company (USUMA) which assured that the three samples were nationally representative. Results: Childhood cancer survivors reported higher education than controls and were less often married. All forms of common mental distress were increased among survivors. Twenty‐four percent of male (N = 526) and 41% of female survivors (N = 425) reported some form of clinically relevant mental health symptoms. Somatic distress as the leading complaint was highly frequent among CCS (OR: 10.98, CI 95%: 7.24‐16.64). Complaints by generalized anxiety (OR: 5.04, CI 95%: 2.61‐9.70), panic (OR: 3.28, CI 95%: 1.60‐6.70), depression (OR: 3.36, CI 95%: 2.22‐5.09), and suicidality (OR = 2.22; CI 95%: 1.38‐3.57) were also strongly increased. Female sex, low education, low income, and unemployment were associated with increased distress. Conclusions: Findings indicate a need to integrate psycho‐oncological screening and care into long‐term aftercare. Somatic distress, as cause and indicator of psychological distress, should receive stronger attention, especially tiredness, low energy, and pain. Abstract : The article compares self‐reported distress by common mental disorders (depression, somatic symptoms, suicidal ideation, generalized anxiety, panic, social anxiety, and sleep disturbances) among adult survivors of childhood cancer (N = 951) with the general population. Survivors suffer more frequently from symptoms of common mental disorders than controls.